2018
DOI: 10.1007/s12178-018-9465-4
|View full text |Cite
|
Sign up to set email alerts
|

Partial and Full-Thickness RCT: Modern Repair Techniques

Abstract: Purpose of Review The purpose of this article is to review the recent literature concerning modern repair techniques related to partial-and full-thickness rotator cuff tears. Recent Findings The understanding of rotator cuff pathology and healing continues to evolve, beginning with emerging descriptions of the anatomic footprint and natural history of rotator cuff tears. Significant controversy remains in treatment indications for partial-thickness rotator cuff lesions as well as optimal surgical repair techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 93 publications
(67 reference statements)
0
12
0
Order By: Relevance
“…The understanding of rotator cuff pathology and healing continues to evolve, beginning with emerging descriptions of the anatomic footprint and natural history of rotator cuff tears [1]. Shoulder anatomy, pathology, and biomechanics place unique stress on the rotator cuff tendons during sports activity [2], whereas smoking, hypercholesterolemia, and genetics have all been shown to influence the development of rotator cuff tearing [3].…”
Section: Introductionmentioning
confidence: 99%
“…The understanding of rotator cuff pathology and healing continues to evolve, beginning with emerging descriptions of the anatomic footprint and natural history of rotator cuff tears [1]. Shoulder anatomy, pathology, and biomechanics place unique stress on the rotator cuff tendons during sports activity [2], whereas smoking, hypercholesterolemia, and genetics have all been shown to influence the development of rotator cuff tearing [3].…”
Section: Introductionmentioning
confidence: 99%
“…The superiority of TTR or TCR for PT-RCT is still controversial as both techniques have yielded good results [ 27 , 28 , 45 ]. Kim et al compared TTR and TCR techniques in a prospective randomised controlled study reporting no differences in functional outcome but a significantly higher retear rate for bursal-side tears in TCR repair (23.3% vs. 3.3%) [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rotator cuff tears may cause significant pain, decreased shoulder mobility, and irreparable damage to the glenohumeral joint. 37 Rotator cuff disorders are highly prevalent and represent the most common cause of shoulder disability in the United States. They are responsible for approximately 30% to 70% of shoulder pain-related conditions and 70% of shoulder-related physician visits while accounting for >4.5 million annual visits in the United States.…”
mentioning
confidence: 99%
“…31,48,56 Reimbursement from the Centers for Medicare & Medicaid Services for a hospital-based shoulder MRI (Current Procedural Terminology code 73221) ranges from $303.51 to $387.01, while reimbursement for a hospital-based shoulder US (Current Procedural Terminology code 76881) ranges from $144 to $189. 37. Studies have suggested that this difference may be even greater within private insurance, where the average MRI reimbursement is $999.67 per patient.…”
mentioning
confidence: 99%